Does teacher evaluation based on student performance predict motivation, well-being, and ill-being? - Cuevas, R.; Ntoumanis, Nikos; Fernandez-Bustos, J.; Bartholomew, K. (2018)
This study tests an explanatory model based on self-determination theory, which posits that pressure experienced by teachers when they are evaluated based on their students’ academic performance will differentially predict teacher adaptive and maladaptive motivation, well-being, and ill-being. A total of 360 Spanish physical education teachers completed a multi-scale inventory. We found support for a structural equation model that showed that perceived pressure predicted teacher autonomous motivation negatively, predicted amotivation positively, and was unrelated to controlled motivation. In addition, autonomous motivation predicted vitality positively and exhaustion negatively, whereas controlled motivation and amotivation predicted vitality negatively and exhaustion positively. Amotivation significantly mediated the relation between pressure and vitality and between pressure and exhaustion. The results underline the potential negative impact of pressure felt by teachers due to this type of evaluation on teacher motivation and psychological health.